2021
DOI: 10.1186/s12887-021-02845-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiple anatomic sites of infarction in a pediatric patient with M. pneumoniae infection, a case report

Abstract: Background Although M. pneumoniae (M. pneumoniae) infections have been associated with various extrapulmonary manifestations, there have been very few documented cases of thrombotic events in pediatrics, and none to our knowledge with such extensive involvement as the patient described here. We aim to contribute to the urgency of discovering the mechanism of the coagulopathy associated with M. pneumoniae infections. Case presentation This 10-year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Recent years have seen an uptick in case reports of splenic infarction associated with infections, as documented in both domestic and international literature. Researchers such as Childer, Hahn, and Yin Wenwen [13][14][15] have reported rare instances of splenic infarction linked to infections like COVID-19, Mycoplasma pneumoniae, and Brucella. However, reports of splenic infarction due to Chlamydia psittaci infection are nonexistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years have seen an uptick in case reports of splenic infarction associated with infections, as documented in both domestic and international literature. Researchers such as Childer, Hahn, and Yin Wenwen [13][14][15] have reported rare instances of splenic infarction linked to infections like COVID-19, Mycoplasma pneumoniae, and Brucella. However, reports of splenic infarction due to Chlamydia psittaci infection are nonexistent.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, infections can lead to endothelial dysfunction of vascular cells, triggering brin formation and platelet adhesion and aggregation, ultimately causing splenic artery thrombosis [16]. Further, evidence indicates that the interplay between coagulation pathways and the complement cascade in Mycoplasma pneumoniae infections could lead to infarctions across various anatomical sites [14]. Given that Chlamydia and Mycoplasma are atypical pathogens, the similarity of their thrombotic mechanisms in infections warrants additional investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Children with Mycoplasma pneumoniae pneumonia (MPP) infection are related to higher risks of blood coagulation and thrombosis. Several studies have shown that pulmonary embolism, stroke, splenic infarction, myocardial infarction and even extensive thrombotic events are associated with Mycoplasma pneumoniae infection in children [ 118 , 119 , 120 , 121 , 122 ]. Furthermore, a recent study demonstrates that elevated D-dimer, specifically >11.1 mg/L (even >5.0 mg/L), would assist in the early diagnosis of thrombosis in MPP [ 123 ].…”
Section: Prediction and Early Recognitionmentioning
confidence: 99%
“…Infection Cytomegalovirus [6][7][8] Epstein-Barr virus [9][10][11][12][13][14][15] Infective endocarditis [16][17][18][19][20][21][22] COVID-19 [23][24][25][26][27][28][29][30][31][32][33][34][35] Dengue virus [36] Mycoplasma pneumoniae [37,38] Malaria [39,40] Scrub typhus [41,42] Aspergillus pericarditis [43] Babesiosis [44] Malignancy including neoplasm and myeloproliferative diseases…”
Section: Causes Of Splenic Infarction Referencesmentioning
confidence: 99%